Chloride Penetration in Coastal Concrete Structures: Field Investigation and Model Development - Weidong Zhuo; Quanzhe Yan; Zhengxian Yang; Shaohong Lin; Kaiqi Lin; Fuqiang He (Advances in Materials Science and Engineering)
Field measurements of 42 in-service reinforced concrete bridges in coastal environments of Southeast China, covering a wide range of service year, span length, and concrete mixture, were carried out to investigate the chloride penetration. 323 sets of chloride measurement data were collected in total and then analysed to optimize the parameters involved in the common chloride diffusion model derived based on Fick’s second law. A modified chloride diffusion model was then proposed, taking into consideration a range of influencing factors including ambient temperature, relative humidity, stress state, carbon dioxide, chloride binding, and ageing. Verification of the modified model with field measurement data was performed. The sensitivity of the chloride diffusion to variations of each parameter was discussed in detail eventually.